New Lights on the Life and Works of Shaikh Dawud al-Fattani - Mohd. Zain Abd. Rahman (Studia Islamika, 2002)
Shaykh Dawud al-Fattani is one of the most prominent scholars among the Muslims of the Malay region. His thoughts serve as a legacy for the generation of our modern time, while his works are the source of knowledge that will last forever. His full name, according to Wan Mohd. Shaghir Abdullah, is Wan Dawud bin Van Abdullah bin Wan Idris bin Wan Abu Bakr bin Wan Ismail (Tok Kaya Pandak) bin Andi Faqih Ali Datok Maharajalela. However, Shaykh Dawud, in his writing introduced himself as Shaykh Dawud bin 'Abd Allah bin ldits al-Jawi al-Fattani al-Malayuwi. He is also known as Shaykh Dawud bin Abdullah bin Senik Faftani. Above all, he is better known among the Malays as Tok Shaykh Dawud Fattani or Shaykh Dawud Patani.DOI: 10.15408/sdi.v9i3.660